Versatile algorithms for the computation of 2-point spatial correlations in quantifying material structure - Cecen, Ahmet; Fast, Tony; Kalidindi, Surya R. (Integrating materials and manufacturing innovation, 2016)
This paper presents a generalized framework along with the associated computational strategies for a rigorous quantification of the material structure in a range of different applications using the framework of 2-point spatial correlations. In particular, we focus on applications requiring different assumptions about the periodicity and/or involving irregular domain shapes and potentially extremely large datasets. Important details of the computational algorithms needed to address these challenges are developed and illustrated with example case studies. Algorithms developed and presented in this work are available at http://dx.doi.org/ https://doi.org/10.5281/zenodo.31329 .